2019
DOI: 10.1016/j.cppeds.2019.100683
|View full text |Cite
|
Sign up to set email alerts
|

Gender affirming medical care of transgender youth

Abstract: The number of gender diverse and transgender youth presenting for treatment are increasing. This is a vulnerable population with unique medical needs; it is essential that all pediatricians attain an adequate level of knowledge and comfort caring for these youth so that their health outcomes may be improved. There are several organizations which provide clinical practice guidelines for the treatment of transgender youth including the WPATH and the Endocrine Society and they recommend that certain eligibility c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 87 publications
0
46
0
1
Order By: Relevance
“…Providers should also be cognizant of inadvertent disclosure via parental insurance claims when discussing PrEP. Currently, all GAHT, including the use of gonadotropin-releasing hormone (GnRH) receptor agonists for puberty suppression, requires parental or legal guardian consent if a youth is under age 18 [ 29 , 30 ].…”
Section: Clinical Vignettementioning
confidence: 99%
“…Providers should also be cognizant of inadvertent disclosure via parental insurance claims when discussing PrEP. Currently, all GAHT, including the use of gonadotropin-releasing hormone (GnRH) receptor agonists for puberty suppression, requires parental or legal guardian consent if a youth is under age 18 [ 29 , 30 ].…”
Section: Clinical Vignettementioning
confidence: 99%
“…This in turn prevents increased gender dysphoria related to these changes. If patients then elect to receive masculinizing or feminizing hormone therapy, prior treatment with pubertal blockade can prevent the need for gender‐affirming surgeries such as thyroid chondroplasty in transgender women 19–21 . Puberty blockade is usually achieved through the use of gonadotropin‐releasing hormone agonists such as goserelin, leuprolide, or histrelin in the form of monthly or quarterly subcutaneous injections 21 …”
Section: Gender‐affirming Hormone Therapymentioning
confidence: 99%
“…If patients then elect to receive masculinizing or feminizing hormone therapy, prior treatment with pubertal blockade can prevent the need for gender-affirming surgeries such as thyroid chondroplasty in transgender women. [19][20][21] Puberty blockade is usually achieved through the use of gonadotropin-releasing hormone agonists such as goserelin, leuprolide, or histrelin in the form of monthly or quarterly subcutaneous injections. 21 These therapies are generally well tolerated and help to suppress pituitary production of luteinizing hormone and follicle-stimulating hormone.…”
Section: G Ender-affirming Hormone Ther Apymentioning
confidence: 99%
“…Neira 39 noted that care professionals should also learn effective and sensitive approaches to communication entailing respectful verbal and non-verbal skills that do not threaten the dignity of transgender individuals. Salas-Humara et al 40 stressed the need to continue acquiring knowledge and teaching competence until the care professionals are confident that they can provide ethical and culturally sensitive care. It was evident from the articles that the provision of ethically and culturally sensitive care is contingent upon the care professionals’ ability to discern personal limitations in knowledge, competence, and consistent endeavors to overcome their limitations.…”
Section: Themesmentioning
confidence: 99%
“…However, many studies suggested that the collaborative role of the healthcare team and the organization cannot be neglected. 27,32 35,40,44,50,52 Grossman 27 emphasized that organizational leaders must develop policies and encourage their staff to provide ethical and sensitive care. Karasic and Fraser 31 noted that the team leaders should lead from the front to offer positive experiences to transgender individuals.…”
Section: Themesmentioning
confidence: 99%